Coronal Correction for Severe Deformity Using Robotic-Assisted Total Knee Arthroplasty - Marchand, Robert C.; Sodhi, Nipun; Khlopas, Anton; Sultan, Assem A.; Higuera, Carlos A.; Stearns, Kim L.; Mont, Michael A. (The Journal of Knee Surgery, 2018)
Although robotic-assisted total knee arthroplasty (TKA) has the potential to accurately reproduce neutral alignment, it is still unclear if this correction is attainable in patients who have severe varus or valgus deformities. Therefore, the purpose of this study was to assess a single surgeon's experience with correcting coronal deformities using the robotic-assisted TKA device. Specifically, we looked at correction of varying degrees of varus and valgus deformity in patients who underwent robotic arm-assisted TKA. A total of 330 robotic-assisted TKA cases performed by a single surgeon were analyzed. Preoperative CT scans were registered to the robotic-assisted software to create a three-dimensional rendering from which coronal alignment was measured. Postoperative coronal alignment measurements were taken in the operating room using the robotic-assisted device after trial component placement. The robotic-assisted device uses optical tracking from navigation probes placed on the distal femur and proximal tibia. The robotic-assisted software can register these probes as bony landmarks to measure coronal alignment in the distal plane of the femoral component and proximal plane of the tibial component. A total of 261 cases were of varus knees, 46 cases were of valgus knees, and 23 cases had 0° preoperative alignment. Severe deformity was defined as 7° or greater deformity. Preoperative neutral alignment was defined as 0°, while postoperative neutral alignment was defined as 0° ± 3°. There were 129 patients with and initial severe varus and 7 patients with an initial severe valgus deformity of 7° or greater. Patients were divided into varus or valgus cohorts, and analysis was performed on the overall cohort, as well as nonsevere (<7°) and severe (7° or greater) deformity cohorts.All 132 knees with initial varus deformity of less than 7° were corrected to neutral (mean 1°, range -1–3°). A total of 82 knees (64%) with 7° or greater varus deformity were corrected to neutral (mean 2°, range 0–3°). However, roughly 30% of patients with severe deformity who were not corrected to neutral were still corrected within a couple of degrees of neutral. There were seven knees with 7° or greater valgus deformity, and all were corrected to neutral (mean 2°, range 0–3°). This study demonstrated that all knees were corrected in the appropriate direction within a few degrees of neutral, and no knees were overcorrected. The implication of this ability to achieve alignment goals on clinical outcomes will need to be evaluated in future studies. The results from this study demonstrate the potential for the robotic-assisted device during TKA in helping surgeons achieve a preoperatively planned desired neutral alignment.
Keywords: total knee arthroplasty; coronal alignment; robotic-assisted TKA